Creating Internet Safe for Women in Indonesia: A Challenge to Gender Equality (A Study of Online Gender-Based Violence concerning Women's Rights from Indonesian Law Perspective) - Evyta Rosiyanti Ramadhani; Ayudya Rizqi Rachmawati; Roro Hera Kurnikova (Pusat Studi Gender Universitas Jember, 2026)
The advancement of digital technology has transformed the way individuals interact, particularly through the Internet and social media. While these platforms offer women greater opportunities for expression and participation in public life, they have also led to a rise in online gender-based violence (OGBV). In Indonesia, the COVID-19 pandemic exacerbated this issue, with a significant increase in cases such as revenge porn and sextortion. Legal instruments such as the Pornography Law and the Information and Electronic Transactions Law (IET Law) often fail to protect victims and, in some cases, contribute to their criminalization. This research investigates the right to be free from violence from the perspective of international human rights law and examines the extent to which Indonesia’s legal framework aligns with these international standards. The study applies a normative legal research, combining statute approach and conseptual approach, to analyze the challenges faced by women in accessing justice when subjected to cyber violence. The research ultimately aims to propose legal and policy recommendations that strengthen the protection of women’s rights in the digital space and advance gender equality in Indonesia. Fulfillment of women's rights to be free from discrimination in the form of OGBV can be achieved by the government's efforts to focus more on addressing the root of this problem, namely by making laws that protect women from violence, especially sexual violence that occurs in the cyberspace and its implementation must be supported by law enforcement officers without any exception.